The impact of commercialisation of the media on the content of the conglomerate-owned community newspapers in South Africa: study of four community newspapers form the Caxton CTP Publishers stable. - Mwangi, Susan W. (My University, 2008)
This dissertation draws on empirical research in the print media to consider the impact of commercialisation on the content ferried in community newspapers. The central argument of market driven theories (Badalsty, 1992; Howley, 2005; Bagdikian, 2004) is that the negative effects of commercial interests and dependency on advertisers can be felt on the news pages. In light of what Gillmor (2004:4) refers to as “corporatisation of journalism” this research explores the various issues and themes discussed in four Johannesburg-based community newspapers, namely, Alex News, Diepkloof Urban News, Rosebank-Killarney Gazette and Fourways Review. The research employs both Qualitative and Quantitative Content Analysis research methods to determine the nature of the publications’ content. The findings of this research indicate that at least two thirds of the content ferried in conglomerate-owned community newspapers has a market-driven slant – meaning that they do not carry high proportions of substantive content. Howley (2005:140) argues that news has become a commercial product that is “shaped, packaged and marketed with a constant eye for profits. Newspapers are businesses dedicated to presenting information within the parameters of profitability”. The desire to please advertisers means that newspapers shun controversial issues, politics and debates for fear of alienating readers. He adds that this aversion is a kind of self-censorship that guarantees that political ideas of public interest do not reach the community and the net result of commercialisation make newspapers content banal. A newspaper operating in a market-driven environment does not, in the words of McManus’ (1994:218), serve the primary purpose of news, which is to explain how the environment is working so that the citizens can make good decisions, particularly civic decisions. The findings of this research have shown that in their current state, conglomerate-owned community newspapers fall short of this journalistic ideal.
Keywords: commercialisation; commmunity newspapers